Effective Educative Mentoring Skills: A Collaborative Effort - Lyn McDonald; Annaline Flint (New Zealand Journal of Teachers' Work)
Teacher induction programmes provide critical support for new teachers moving into teaching. The focus of this paper is to examine and identify the specific understandings, attitudes and skills educative mentors require in supporting Provisionally Registered Teachers’ (PRTs) learning. The research for this paper is based on a qualitative approach grounded in the interpretive tradition. Qualitative data were collected from 17 mentor teachers in the form of semi-structured one-to-one interviews which were audio-taped, transcribed and analysed using a thematic approach. Based on the findings the specific understandings, attitudes and skills required by mentor teachers in effective educative mentoring with PRTs are: excellent curriculum and pedagogical knowledge, being an effective and reflective practitioner, clear communication skills, and personal skills of supportiveness and understanding. These findings are important for professional development and practice in induction and mentoring programmes in New Zealand. The findings of this study and the implications that have arisen must be considered within the context and size of the study.